The Limits of Considering Competence in Marriage Contracts: Between Jurisprudential Foundations and Legislative Regulation. A Comparative Jurisprudential and Legal Analytical Study under Law No. 10 of 1984 and its Amendments. (Al-Farooq Journal of Sciences, 2026)
This research addresses the issue of compatibility in marriage contracts as one of the most important jurisprudential and legal issues, directly impacting the objectives of marriage and family stability. The study's central problem lies in defining the concept of compatibility and its criteria, the extent to which it is considered a condition for a valid marriage contract, and the effect of its violation on the contract's validity and continuity. This is explored in light of the multiplicity of jurisprudential opinions and the varying supporting evidence, coupled with the ambiguity of the legal nature of the compatibility condition and its implications for judicial application. The research's scholarly significance lies in its treatment of an issue that remains a subject of jurisprudential and legal debate, while attempting to connect it to Libyan legislation. This contributes to enriching specialized studies in family law and personal status matters. Its practical importance stems from addressing an issue that touches people's daily lives, as evidenced by the increasing number of cases in courts seeking annulment of marriage contracts due to incompatibility.This underscores the importance of the research. The researchers employed a descriptive-analytical and comparative approach in their study, examining jurisprudential trends, analyzing legal texts, and comparing them.They concluded with findings and recommendations that contribute to achieving a balance between the objectives of Islamic law and the requirements of family stability.
Keywords: Compatibility in marriage – Jurisprudential perspective – Libyan legislation